Kajian Penataan Tata Hijau Di Ruang Jalan Ditinjau Dari Persepsi Visual Studi Kasus: Jalan Solo, Jalan Suroto, dan Ring Road Utara Yogyakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
This research was intended to study the direction of green-structure design in road space, as well as formulation of design factor affecting green-structure visually in road space, which is an unseparated part from urban development. Making the vegetation element as important element in road space is a suggested item, since vegetation can engineered environment, so that it creates an urban greening which embodying an environmental-soundly zone, cool condition, natural environment, soft, harmony-beautiful, and convenience. The research method was computer simulation, an assessement based on visual perception of respondent over the simulation display output of green-structure within road space. The research was conducted using "semantic differential" method which is a levelled assessment over tendency to one word of words pair of assessment was used. The result based on assessment of respondent's visual perception on green-structure simulation in road space in outline included : 1) crown combination giving image that road space permanently, be spacious, clear, person not unpressed, cool, convenient, shady, natural, and soft, so this condition is preferred and vice versa